Synergy Between Customary and Islamic Law: The Transformation of Restorative Justice in The Aceh Judicial System - Taufikurahman, Rizky; Saputro, Triyono Adi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Indonesia, as a country with a pluralistic legal system, exhibits interactions among state law, customary law, and religious law in law enforcement practices. Aceh is a region that shows the strongest interaction between customary law and Islamic law, which are historically and sociologically understood as a single normative entity, as reflected in the philosophy of hukom ngon adat lagee zat ngon sifeut. This article analyzes the forms and patterns of interaction between Acehnese customary law and Islamic law in restorative justice practices, the mechanisms for resolving cases through Acehnese customary institutions, and the challenges and legal implications of their implementation within Indonesia’s national legal system. This research employs normative legal research methods, including statutory, conceptual, and historical approaches, supported by a review of relevant literature and legal documents. The results indicate that restorative justice practices in Aceh are grounded in the integration of customary and Islamic law values, emphasizing deliberation, forgiveness, compensation, and the restoration of social relations, particularly in resolving cases of minor assault, domestic conflict, and violations of moral norms. However, the implementation of customary and sharia-based restorative justice still faces challenges, including disharmony with national law, differing perceptions of justice, and limited formal legitimacy. Therefore, regulatory harmonization and institutional strengthening are needed so that restorative justice practices grounded in customary and Islamic law in Aceh can function effectively and fairly, and align with the principles of a modern rule of law.